The Use of Facebook in Blended Course in Teacher Training College - Milya Sari (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Future educational challenges are related to technology, especially information and communications technology (ICT). The ICT has a very big influence to the learners. Many students have already used social media ‘facebook’ and ‘twitter’, but not so with their teachers. The rapid globalization and ICT development requires a change in attitude and mindset of teachers and students, including in Teacher Training College (LPTK). A good approach is to integrate technology with education through blended learning models (BLM), that is learning that combines face-to-face learning activities and learning online through social media facebook. One of the advantages of BLM is to improve the interaction between learners, between learners and educators, and learners with different learning resources anytime and anywhere without being limited by space and time.